Genetic Improvement of Peanut Cultivars for West Africa Evaluated with the CSM‐CROPGRO‐Peanut Model. (1st November 2015) - Narh, Stephen; Boote, Kenneth J.; Naab, Jesse B.; Jones, J.W.; Tillman, Barry L.; Abudulai, Mumuni; Sankara, Philippe; M'Bi Bertin, Zagre; Burow, Mark D.; Brandenburg, Rick L.; Jordan, David L.
Abstract : Crop models are valuable tools for evaluating past genetic improvement as well as guiding future breeding strategies for target regions. The objective of this study was to use the CSM‐CROPGRO‐Peanut model to evaluate traits responsible for genetic improvement of peanut ( Arachis hypogaea L.) genotypes grown in West Africa. Data on19 cultivars were obtained from performance trials in 2010 and 2011 at two sites in Ghana and two sites in Burkina Faso. For all sites and years, pod yield, seed yield, shelling percentage, and seed size were determined at harvest, and leaf spot disease was recorded. Time‐series data on crop biomass, pod mass, and pod harvest index were measured at two Ghana sites in 2 yr. Data on phenology, e.g., first flower, first pod, and harvest maturity were observed at one site in Ghana in 2010. Optimization and calibration procedures were used with the CROPGRO‐Peanut model to estimate cultivar coefficients from the data. The derived cultivar coefficients simulated pod yields that agreed well with observed pod yields. Solved cultivar coefficients varied considerably among cultivars. With the derived cultivar coefficients, the CROPGRO‐Peanut model was able to simulate much of the genetic variation in pod yield among the 19 cultivars within eight site‐year combinations ( d statistic of 0.90 and RMSE of 299 kg ha −1 ). The derived cultivar coefficients illustrated that yield improvement leading to nearly twofold higher pod yield resulted from a combination of improved partitioning (leading to higher pod harvest index), higher photosynthesis, longer life cycle, longer seed‐filling duration, and improved leaf spot resistance.